2011
DOI: 10.1111/j.1742-6723.2011.01435.x
|View full text |Cite
|
Sign up to set email alerts
|

Emergency medicine and futile care: Taking the road less travelled

Abstract: Debate around medical futility has produced a vast literature that continues to grow. Largely absent from the broader literature is the role of emergency medicine in either starting measures that prove to be futile, withholding treatment or starting the end of life communication process with patients and families. In this discussion we review the status of the futility debate in general, identify some of the perceived barriers in managing futile care in the ED including the ethical and legal issues, and establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 21 publications
0
37
0
1
Order By: Relevance
“…O'Connor et al indicated that in EDs, clinicians often play the role of commencing measures which might be judged to be futile in retrospect, and they argue that the ED environment could be an ideal place for difficult conversations, and difficult decisions regarding withholding of treatment [31]. They also indicated that treatment uncertainty is difficult to measure as it is usually the result of attempting to reach a consensus.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…O'Connor et al indicated that in EDs, clinicians often play the role of commencing measures which might be judged to be futile in retrospect, and they argue that the ED environment could be an ideal place for difficult conversations, and difficult decisions regarding withholding of treatment [31]. They also indicated that treatment uncertainty is difficult to measure as it is usually the result of attempting to reach a consensus.…”
Section: Resultsmentioning
confidence: 99%
“…They also indicated that treatment uncertainty is difficult to measure as it is usually the result of attempting to reach a consensus. Medical futility has been defined both quantitatively by the probability of the success of a treatment and qualitatively by the perceived value in terms of quality of life [31]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among several similar definitions, for example, the American College of Emergency Physicians (ACEP) defines the specialty of EM as a medical specialty dedicated to the diagnosis and treatment of unforeseen illness or injury. [14][15][16][17][18] According to the World Health Organization (WHO), between 2015 and 2050, the proportion of the world's population over 60 years will double, and by 2050 there will be more than 400 million people aged 80 and older worldwide. Notably, among the elderly population, only 15% of all deaths are due to an acute disease or trauma, whereas 85% are related to chronic diseases.…”
Section: Introductionmentioning
confidence: 99%